Clinical Characteristics and Aqueous Humor Laboratory Analysis of Chinese Patients With Rubella Virus-Associated and Cytomegalovirus-Associated Fuchs Uveitis Syndrome - Kang, Hao; Bao, Han; Shi, Yanhong; Feng, Jing; Yang, Weiqiang; He, Yinzhang; Wang, Hui; Hu, Xiaofeng; Tao, Yong (Frontiers in Medicine, 2020)
Purpose: To describe and compare the clinical characteristics and laboratory analysis results of aqueous humor (AH) in fuchs uveitis syndrome (FUS) patients caused by rubella virus (RV) and cytomegalovirus (CMV). Methods: A retrospective and observation-based study was performed on 32 patients with FUS. Etiologies, clinical characteristics, ocular complications, visual prognoses, inflammatory cytokines and virus-specific antibodies in AH were compared. Results: Among all the cases involved, 24 had RV FUS and 8 had CMV FUS. The mean age at diagnosis of FUS in the CMV group was older than that of the RV group (P=0.031). The mean LogMAR best corrected visual acuity (BCVA) at initial presentation and at the final visit were both significantly higher in the CMV FUS group than those in the RV FUS group (P=0.004, P=0.047). The highest intraocular pressure (IOP) was significantly higher in the CMV group (P=0.040). Consistent with elevated IOP, the CMV FUS patients were significantly more prone to developing glaucoma eventually than the RV FUS patients (P=0.039). Vitreous opacity was found in 66.7% of the RV patients and 25.0% of the CMV patients (P=0.038). The gender ratio, initial symptoms, presence and types of keratic precipitates, severity of anterior segment inflammation, iris lesions, and incidence of complicated cataract were similar between the two groups. There was no detectable difference of inflammatory cytokines in AH between RV FUS and CMV FUS. Conclusion: The clinical manifestations and disease prognosis vary between CMV FUS and RV FUS. However, clinical differences are always not obvious enough for differential diagnosis. The laboratory AH analysis is necessary to identify the etiology, determine the therapeutic strategies, and assess the disease prognosis.